PATIENT SAFETY CULTURE IN PUBLIC GENERAL HOSPITALS: LITERATURE REVIEW - Fauziyyah, Rifa; Basabih, Masyitoh (UI Scholars Hub, 2023)
Background: The global prevalence of preventable adverse events in healthcare is a significant problem, with approximately 42.7 million annual accidents resulting in 23 million DALYs lost. Safety culture plays a crucial role in mitigating or exacerbating these incidents within hospitals. Objectives: To identify the results of the assessment of patient safety culture and the characteristics associated with patient safety culture in public general hospitals in various countries. Methods: This study was conducted between April-July 2021 utilizing a literature review approach using study searches through PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda databases, and it discovered 17 papers from 2011-2021 that used the Hospital Survey on Patient Safety Culture (HSOPSC) as an instrument to assess patient safety culture. Results: This study found that patient safety culture at public general hospitals remains low, and hospital staff perception of safety has to be improved. Discussions: “Teamwork in hospital units” receives the most favorable replies, while “non-punitive response to error” receives the least positive responses. The majority of the employees assessed patient safety in their work unit as “excellent/very good/acceptable” and reported no incidents in the previous year. Staff and hospital characteristics were also found to be related to patient safety culture.